2020
DOI: 10.1186/s12870-020-02562-6
|View full text |Cite|
|
Sign up to set email alerts
|

A 2-Cys peroxiredoxin gene from Tamarix hispida improved salt stress tolerance in plants

Abstract: Background: Peroxiredoxins (Prxs) are a large family of antioxidant enzymes that respond to biotic and abiotic stress by decomposing reactive oxygen species (ROS). In this study, the stress tolerance function of the Th2CysPrx gene was further analysed. It lays a foundation for further studies on the salt tolerance molecular mechanism of T. hispida and improved salt tolerance via transgenic plants. Results: In this study, the stress tolerance function of the Th2CysPrx gene was further analysed. The results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…In this work, we identify a chloroplast localized 2-Cys Prx encoding gene TaBAS1 ( Figure 1 ), and its overexpression obviously enhances salt tolerance in wheat and Arabidopsis ( Figures 3 , S3 ) ( Xu et al., 2016 ). In line with the reports that the enhancement of salt tolerance by 2-Cys Prxs from Suaeda salsa L. and Tamarix hispida ( Jing et al., 2006 ; Wang et al., 2020 ), our data indicate that the role of 2-Cys-Prxs in salt tolerance is conserved in different plants. Moreover, TaBAS1 enhances grain yield of wheat under salt stress, but has no adverse effect on the growth and yield under the control condition ( Figure 7 ), exhibiting its potential in the germplasm improvement of wheat without imposing the trade-offs between yield and tolerance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this work, we identify a chloroplast localized 2-Cys Prx encoding gene TaBAS1 ( Figure 1 ), and its overexpression obviously enhances salt tolerance in wheat and Arabidopsis ( Figures 3 , S3 ) ( Xu et al., 2016 ). In line with the reports that the enhancement of salt tolerance by 2-Cys Prxs from Suaeda salsa L. and Tamarix hispida ( Jing et al., 2006 ; Wang et al., 2020 ), our data indicate that the role of 2-Cys-Prxs in salt tolerance is conserved in different plants. Moreover, TaBAS1 enhances grain yield of wheat under salt stress, but has no adverse effect on the growth and yield under the control condition ( Figure 7 ), exhibiting its potential in the germplasm improvement of wheat without imposing the trade-offs between yield and tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…Note that TaBAS1 overexpression enhances the tolerance to H 2 O 2 in wheat but not Arabidopsis ( Figure S4 ), which may owe to the difference in the response threshold to H 2 O 2 treatment that need to be studied in the future. Moreover, TaBAS1 promotes the activities of ROS scavenging enzymes SOD, GPX and CAT ( Figures 5A–C ), consistent with the previous studies that 2-Cys Prxs elevate these ROS scavenging enzymes in other plants ( Pulido et al., 2010 ; Wang et al., 2020 ; Xu et al., 2022 ). This indicates that 2-Cys Prxs can affect the ROS scavenging system to efficiently remove excessive ROS together.…”
Section: Discussionsupporting
confidence: 91%
“…ThSAP30BP may play an important physiological role in the salt tolerance of T. hispida [ 23 ]. The 2-Cys peroxidase gene of this plant improves its tolerance to salt stress [ 24 ]. ThNAC7 induces the transcriptional levels of genes associated with stress tolerance to enhance salt and osmotic tolerance by increasing osmotic potential and enhanced ROS scavenging capability [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the proteins whose expression levels were elevated upon exposure to high temperatures, were associated with the process of stress tolerance. Cationic peroxidase 1 (Li et al 2020), phosphoserine phosphatase (Ho and Saito 2001), and peroxiredoxins (Wang et al 2020), were associated with responses to biotic and abiotic stresses that entailed the decomposition of reactive oxygen species and prevention of changes to cell membrane permeability. Expression levels of E3 ligase (Stone 2019), Hul5 HECT ubiquitin ligase (Fang et al 2011), and F-box protein (Li et al 2018) showed an increase in some temperatures, and a decrease in other temperatures.…”
Section: Discussionmentioning
confidence: 99%